2019
DOI: 10.1111/ejn.14635
|View full text |Cite
|
Sign up to set email alerts
|

Biological bases of suicidal behaviours: A narrative review

Abstract: In humans, suicide overrides the basic instinct of survival that is common to the vast majority of known life forms. This phenomenon has frightened and fascinated philosophers throughout history. This virtually exclusively human behaviour has been and still is a major issue worldwide, thus explaining its place first in religious and philosophical doctrines, then in sociology and philosophy, and currently in biology and medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 200 publications
(248 reference statements)
0
38
0
2
Order By: Relevance
“…Suicidal behaviour has been linked to impulsive aggression, 59 impaired executive function and inhibition, 60 and altered decision-making. 61 These factors have also been observed in patients with BD. Impaired executive function, particularly impaired decision making and impulsivity, 62 66 has been linked to an increased risk of suicidal and NSSI behaviour.…”
Section: Discussionmentioning
confidence: 84%
“…Suicidal behaviour has been linked to impulsive aggression, 59 impaired executive function and inhibition, 60 and altered decision-making. 61 These factors have also been observed in patients with BD. Impaired executive function, particularly impaired decision making and impulsivity, 62 66 has been linked to an increased risk of suicidal and NSSI behaviour.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies reported alterations of the serotoninergic (e.g., serotonin depletion), glutamatergic (e.g., alteration of the kynurenine pathway), and inflammatory systems (e.g., increased levels of proinflammatory cytokines), as well as neuroplasticity [e.g., low levels of brain-derived neurotrophic factor (BDNF)] in SB ( 6 ). Psilocybin is rapidly metabolized into its active metabolite psilocin that is a serotoninergic agonist with high affinity for 5-HT2A receptors (5-HT2AR) ( 1 ).…”
Section: Biological Pathways Implicated In Sb On Which Psilocybin Actmentioning
confidence: 99%
“…Psilocybin intake results in a rapid increase in 5-HT2AR activity that might lead to higher BDNF expression and consequently to major synaptic changes ( 7 ) and might promote neuroplasticity. Postmortem studies showed that 5-HT2AR availability is increased in the brain of suicide victims, possibly due to genetic variations or compensatory mechanisms ( 6 ). Therefore, psilocybin-positive effect on neuroplasticity and the serotoninergic system could contribute to compensate SB-related impairment of these systems.…”
Section: Biological Pathways Implicated In Sb On Which Psilocybin Actmentioning
confidence: 99%
See 2 more Smart Citations